Modelos de intervención psicosocial en situaciones de desastre por fenómeno natural (2012)
ABSTRACT: The Universidad de Antioquia summoned to The Center of Public Opinion - CEO - with the support of the Faculty of Social Sciences and Human, to construct the space of the observatory of the public opinion that will constitute a social and politics participating tool in a pursuit to the changes of the public opinion that are taking place daily. Methodologically, the primary idea is the studies of the public opinion by an strategy of panel, of the social processes (electoral, ethical, actitudinales, socio-economic characterizations).